Severe circulatory failure caused by acute cardiac dysfunction in a young man with leptospirosis living in a slum of Rome, Italy (REV JI-PH-D-24–01876R3) - Salvatore Lucio Cutuli; Fabiana Rizzo; Gennaro De Pascale; Silvia Costantini; Anna Maria Marella; Massimo Antonelli; Alessandra Ciervo (Journal of Infection and Public Health)
Leptospirosis may cause severe disease characterized by acute kidney injury, hepatic failure, or multiorgan dysfunction, including cardiac manifestations. The incidence and severity of cardiac involvement in leptospirosis are underreported and poorly understood. Moreover, left ventricular dysfunction is considered a rare complication in seen in leptospirosis cases. We present a case of leptospirosis in a 19-year-old male, living in a slum in Rome-Italy, without a previous cardiovascular history, who developed septic shock, and severe non-ischemic left ventricular systolic dysfunction following leptospirosis infection. In this setting, the patient developed KDIGO stage 3 acute kidney injury and acute circulatory failure, and requiring high dose norepinephrine and dobutamine. Empiric wide-spectrum antibiotic therapy with Piperacillin-Tazobactam was started early after the recognition of sepsis, and was deemed appropriate after the serological confirmation of leptospirosis. Patient’s clinical condition progressively improved and he was discharged after 21 days of hospital stay (6 of those were in the intensive care unit), with full organ function recovery.To conclude, this case report supports the need for preventive public health interventions aiming to reduce the burden of environmentally transmitted life-threatening infectious diseases, including leptospirosis, by promoting sanitation and infrastructures, in order to prevent unequal health outcomes.